e-Learning Systems, Environments and Approaches: Theory and Implementation - Isaias, P.; Spector, M.; Ifenthaler, D.; Sampson, Demetrios (Springer International Publishing, 2015)
Digital technologies and Information Systems (IS) are playing an increasing role in the planning, design and implementation of e-learning systems and environments. These developments have led to new research challenges that are discussed in this volume. This book entitled E-Learning Systems, Environments and Approaches: Theory and Implementation captures the current state-of-the-art in Exploratory Learning Technologies (Part I), e-Learning Social Web Design (Part II), Learner Communities through e-Learning Implementations (Part III) and Collaborative and Student-Centered e-Learning Design (Part IV). The volume consists of twenty chapters of expanded versions of highly rated peer-reviewed papers presented at the CELDA (Cognition and Exploratory Learning in the Digital Age) 2013 Conference as well as contributions from scholars from around the world who were invited to contribute on specific topics.